2021
DOI: 10.1002/alz.12511
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease biomarkers in Black and non‐Hispanic White cohorts: A contextualized review of the evidence

Abstract: Black Americans are disproportionately affected by dementia. To expand our understanding of mechanisms of this disparity, we look to Alzheimer's disease (AD) biomarkers. In this review, we summarize current data, comparing the few studies presenting these findings. Further, we contextualize the data using two influential frameworks: the National Institute on Aging–Alzheimer's Association (NIA‐AA) Research Framework and NIA's Health Disparities Research Framework. The NIA‐AA Research Framework provides a biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 112 publications
(258 reference statements)
2
55
0
Order By: Relevance
“…Data has shown that biomarker changes in AD can vary between Blacks and Whites, and similar biomarker profiles can be associated with divergent cognitive function. 37 To date, it is unknown how frequently biomarker testing of asymptomatic persons is pursued in clinical practice. Surveys conducted prior to the approval of amyloid PET scans for clinical use found that a majority of dementia specialists planned to use them to identify asymptomatic persons at risk for AD dementia, 38 while others would be reluctant to share results for fear of negative psychosocial outcomes.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
See 2 more Smart Citations
“…Data has shown that biomarker changes in AD can vary between Blacks and Whites, and similar biomarker profiles can be associated with divergent cognitive function. 37 To date, it is unknown how frequently biomarker testing of asymptomatic persons is pursued in clinical practice. Surveys conducted prior to the approval of amyloid PET scans for clinical use found that a majority of dementia specialists planned to use them to identify asymptomatic persons at risk for AD dementia, 38 while others would be reluctant to share results for fear of negative psychosocial outcomes.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
“…The limited inclusiveness of biomarker research raises concerns about the validity of biomarker data in these populations. Data has shown that biomarker changes in AD can vary between Blacks and Whites, and similar biomarker profiles can be associated with divergent cognitive function 37 …”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
See 1 more Smart Citation
“…The limited inclusiveness of biomarker study samples raises concerns about the validity and reliability of biomarker data in underrepresented groups [ 19 ]. Data shows that biomarker changes in AD can vary between Black/African American and White populations, and similar biomarker profiles can be associated with divergent cognitive function [ 20, 21 ]. The current lack of reliable biomarker data for underrepresented groups limits the diagnostic, prognostic, and therapeutic validity of biomarkers for clinical use in these populations, and has the potential to further exacerbate health disparities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individual factors modify the relationship between tau accumulation and cognition, with younger age, female sex, higher educational attainment, and higher baseline cortical thickness all associated with increased resistance against the deleterious effect of pathology on cognitive performance (30). Some studies suggest that the relationship between tau, neurodegeneration, and cognition may also vary with race and ethnicity as proxies for social determinants of health (31), though much more work on diverse cohorts is needed to better understand these relationships. Finally, the development of biomarkers that measure common non-AD pathologies (e.g., vascular lesions, TDP43, and a-synuclein aggregates) will be critical for achieving a more adequate prognosis, as these processes are highly prevalent in patients with AD (32) and contribute significantly to neurodegeneration and cognitive decline.…”
mentioning
confidence: 99%